2023
DOI: 10.1101/2023.06.09.23291215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apolipoprotein E moderates the association between Non-APOEPolygenic Risk Score for Alzheimer’s Disease and Aging on Preclinical Cognitive Function

Abstract: INTRODUCTION: Variation in preclinical cognitive decline suggests additional genetic factors related to Alzheimer's disease (e.g., a non-APOE polygenic risk scores [PRS]) may interact with the APOE ε4 allele to influence cognitive decline. METHODS: We tested the PRS×APOE ε4×age interaction on preclinical cognition using longitudinal data from the Wisconsin Registry for Alzheimer's Prevention. All analyses were fitted using a linear mixed-effects model and adjusted for within individual/family correlation among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Past epidemiological studies have investigated how lifestyle choices affect the genetic risk of LOAD, yielding mixed results 15,16,39,40 , with some null findings even in a large sample 15 . Recent research has demonstrated that age modifies LOAD genetic risk 18,41,42 and that PRS effects on LOAD-related traits are stronger among APOE-ε4 carriers 22,[43][44][45] . However, these findings have not been integrated into previous genelifestyle interaction analyses, as the present analysis does.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Past epidemiological studies have investigated how lifestyle choices affect the genetic risk of LOAD, yielding mixed results 15,16,39,40 , with some null findings even in a large sample 15 . Recent research has demonstrated that age modifies LOAD genetic risk 18,41,42 and that PRS effects on LOAD-related traits are stronger among APOE-ε4 carriers 22,[43][44][45] . However, these findings have not been integrated into previous genelifestyle interaction analyses, as the present analysis does.…”
Section: Resultsmentioning
confidence: 99%
“…First, adhering to a healthy lifestyle might influence when genetic effects become noticeable throughout one’s life. Prior work suggested adverse PRS effects emerged by age 70 in APOE-ε4 carriers 22 . The present analysis in the same cohort suggests that among APOE-ε4 carriers with the least healthy habits, cognitive decline begins approximately 1-3 years earlier, although this was not replicated in HRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation